Influence of Surface Tilt Angle on a Chromatic Confocal Probe with a Femtosecond Laser - Ryo Sato; Yuki Shimizu; Hiraku Matsukuma; Wei Gao (Applied Sciences, 2022)
This paper presents an intentional investigation of the effect of the object tilt angle on the tracking local minimum method (TL method), which is the one for detecting the measurement target position of the object optical axis, in a chromatic confocal probe employing a differential dual-fiber-detector optical system with a mode-locked femtosecond laser as the light source. The effect of the object tilt angle on dual-detector confocal probes, and even chromatic confocal probes, has not been investigated in detail so far, although the effect of object tilt angle on scanning confocal probes has been studied. At first, to examine the influence of the object tilt angle on the TL method, a theoretical model is established, and numerical simulations are performed based on the established theoretical equation. Then, the effect of aberrations in confocal optics on the confocal response curve is investigated in experiments. Finally, investigations on the effect of the object tilt angle on the TL method are demonstrated in experiments.